Impact of succession planning practices on employee relations among health professionals in one government hospital in Zimbabwe - Mabhanda, Wilson; Masukume, Herbert (goodwood publishing, 2025)
Purpose: This study ascertains how succession-planning practices affect employee relations in public healthcare facilities in Zimbabwe. Research Methodology: The pragmatism philosophy, which emphasizes relevance in interpreting mixed-method data, served as the foundation for this study. A sample size of 60 respondents was chosen from 120 healthcare professionals. A descriptive method was used for data analysis using SPSS and theme analyses. Results: The results revealed that although succession planning exists in healthcare institutions, its implementation is shambolic, heightening its negative impact on employee relations, as evidenced by high staff turnover. Limitations: Despite adopting a mixed-method approach, the findings could not unravel the effective implementation of succession planning in the whole country; hence, the results from one institution cannot be generalized. Contribution: Effective succession planning results in better employee relationships, lower uncertainty, increased engagement, and boosted morale among staff members. It can also broaden our understanding of best practices in succession planning.